2020
DOI: 10.3390/ijms21186761
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Extracellular Vesicle-Associated TSG-6 from Adipose Mesenchymal Stromal Cells in Traumatic Brain Injury

Abstract: Multipotent mesenchymal stromal cells (MSC) represent a promising strategy for a variety of medical applications. Although only a limited number of MSC engraft and survive after in vivo cellular infusion, MSC have shown beneficial effects on immunomodulation and tissue repair. This indicates that the contribution of MSC exists in paracrine signaling, rather than a cell-contact effect of MSC. In this review, we focus on current knowledge about tumor necrosis factor (TNF)-stimulated gene-6 (TSG-6) and mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 142 publications
0
16
0
Order By: Relevance
“…During the past decade, a large number of experimental studies provided evidence about beneficial effects of MSC-Exos in the treatment of Alzheimer disease, Parkinson disease, post-traumatic and ischemic brain injury, schizophrenia, and autism spectrum disorders (ASD) ( Table A1 ) [ 12 , 13 , 14 , 15 , 16 , 17 ]. In this review article, we emphasized their findings, indicating MSC-Exos as potentially new therapeutic agents for the treatment of neurocognitive diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, a large number of experimental studies provided evidence about beneficial effects of MSC-Exos in the treatment of Alzheimer disease, Parkinson disease, post-traumatic and ischemic brain injury, schizophrenia, and autism spectrum disorders (ASD) ( Table A1 ) [ 12 , 13 , 14 , 15 , 16 , 17 ]. In this review article, we emphasized their findings, indicating MSC-Exos as potentially new therapeutic agents for the treatment of neurocognitive diseases.…”
Section: Introductionmentioning
confidence: 99%
“…TSG-6 has been associated with the regulation of pro-inflammatory cytokines and the augmentation of tissue repair in various animal models while suppressing inflammatory reactions triggered by ischemia in the heart and thereby limiting the destruction of cardiomyocytes [ 48 , 52 , 53 , 54 , 55 , 84 ]. TSG-6 gene inactivation has been associated with the upregulation of inflammatory immune reactions, while the over-expression of the TSG-6 gene has been associated with the downregulation of inflammatory reactions [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impacts from sports, car crashes, military experiences, or falls can lead to damage to the brain called a concussion, or traumatic brain injury (TBI). Originally thought to be an acute event, research has now shown that TBIs can lead to long-lasting effects on brain function, reducing life expectancy [308,309,314]. TBIs produce immediate trauma to the brain in which neurons, glia, and blood vessels stretch or tear, inducing apoptosis and damaging the BBB.…”
Section: Brain Injurymentioning
confidence: 99%